0
$\begingroup$

Help me solve this problem! I have tried it many times but nothing appeared. This is the question: If a:b=c:d=e:f, prove that each is equal to (a+c-e):(b+d-f).

$\endgroup$
0
$\begingroup$

Let $$\frac ab=\frac cd=\frac ef=k$$

$\implies Xa+Yc+Ze=k(Xb+Yd+Zd)$

$\endgroup$
  • $\begingroup$ Thank you but I need more solution but my teacher left me clues and I don't know if it is correct or not: a/b=c/d=e/f=a+c-e/b+d-f a=bk, c=dk, e=fk and I don't know what to do next, please help. $\endgroup$ – Wilson Royce Ong King Oct 16 '14 at 11:09
  • $\begingroup$ @WilsonRoyceOngKing, Here $$X=Y=1, Z=-1$$ $\endgroup$ – lab bhattacharjee Oct 16 '14 at 11:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.